2022
DOI: 10.3389/fcell.2022.751367
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Oncogenic RAS on Chemotherapy and Radiotherapy Resistance Through DNA Repair Pathways

Abstract: RAS oncogenes are chief tumorigenic drivers, and their mutation constitutes a universal predictor of poor outcome and treatment resistance. Despite more than 30 years of intensive research since the identification of the first RAS mutation, most attempts to therapeutically target RAS mutants have failed to reach the clinic. In fact, the first mutant RAS inhibitor, Sotorasib, was only approved by the FDA until 2021. However, since Sotorasib targets the KRAS G12C mutant with high specificity, relatively few pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…However, the effect of BBOX1-AS1 on radiotherapy sensitivity in CRC cells is unknown. It is well known that radiotherapy resistance often leads to a poor response to therapy [ 27 , 28 ]. Therefore, our findings provide novel ideas for the clinical treatment of radiotherapy resistance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of BBOX1-AS1 on radiotherapy sensitivity in CRC cells is unknown. It is well known that radiotherapy resistance often leads to a poor response to therapy [ 27 , 28 ]. Therefore, our findings provide novel ideas for the clinical treatment of radiotherapy resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical data demonstrated that KRAS mutations might induce chemo and radio-resistance via multiple mechanisms, such as the induction of senescence, imbalance in ROS production, and activation of mechanisms of DNA repair [ 127 ]. Importantly, resistance to radiation has also been demonstrated in some clinical reports [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with heightened MAPK/ERK activity exhibited increased numbers of CD204 + positive cells, which identifies macrophages with pro-tumorigenic functions 67,68 . In contrast, MYC-overexpressing patients showed increased infiltration of S1009 + immunosuppressive myeloid cells 69,70 . Thus, these results provide further evidence of the distinct impact Myc and MAPK/ERK exert on myeloid cell education, which correlated with poor patient prognosis (Fig.…”
Section: Distinct Oncogenic Signaling Pathways Modulates the Systemic...mentioning
confidence: 92%